Application of Robust Approach to Capacitated Location of Collection Sites and Capacitated Vehicle-routing Problem Model in an Urban Waste Management System - Mohammad Hossein Kabgani; Hamid Shahbandarzadeh; Ebrahim Heidari; Nooraldin Amiri (Environmental Energy and Economic Research)
In the present study, a model including two robust objective functions to reduce costs related to the location of waste transfer facilities in Bushehr. Using the first objective function not only reduces the selection of collection sites but also ensures the overall cost associated with the collection phase. In addition, the first objective function of this research seeks to optimally allocate citizens to collection sites. Also, this model includes the types of bins required for allocation to collection sites so that the total demand of the area is met. Another result of this objective function is that the landfills allocated to these sites may be of different types, with different distances from citizens' homes and even different capacities. Finally, each citizen receives service through a waste collection site with the shortest distance from home to the collection point. The second robust objective function to minimize total collection distance has been discussed. Waste collection widely depends on the route optimization problem that involves a large amount of expenditure in terms of capital, labor, and variable operational costs. Thus, the more waste collection route is optimized, the more reduction in different costs and environmental effect will be. This study proposes a modified robust optimization in a capacitated vehicle routing problem (CVRP) model to determine the best waste collection and route optimization solutions. Other results of this research show that the value of the objective functions determined in the robust method is less than the definite method.